Character Creation Technology in Video Games: Enhancing Player Immersion - Qurbonov Xurshid Narzulla o’g’li (Genius Journals, 2023)
This article explores the role of character creation technology in video games and its significant impact on enhancing player immersion. With the advancements in gaming technology, developers have introduced increasingly sophisticated character creation tools that allow players to customize their in-game avatars, tailoring them to their personal preferences and creative visions. The article examines how these tools not only provide players with a sense of ownership and agency over their virtual personas but also contribute to a more immersive gameplay experience
Keywords: Character creation technology; video games; player immersion